Job placement agencies in an artificial labor market - Marcin Wozniak (Economics: The Open-Access, Open-Assessment E-Journal, 2016)
In this paper, an agent-based search and matching (ABSAM) model of a local labor market with heterogeneous agents and an on-the-job search is developed, i.e. job seekers who vary in unemployment duration, skills levels and preferences compete for vacancies which differ for skills demands and the sector of the economy. Job placement agencies help unemployed persons find appropriate job vacancies by improving their search effectiveness and by sharing job advertisements. These agents cooperate in an artificial labor market where the key economic conditions are imposed. The interactions between the participants are drawn directly from labor market search theory. The main research task was to measure the direct and indirect impacts of labor market policies on labor market outcomes. The global parameters of the ABSAM model were calibrated with the Latin hypercube sampling technique for one of the largest urban areas in Poland. To study the impact of parameters on model output, two global sensitivity analysis methods were used, i.e. Morris screening and Sobol indices. The results show that the job placement agencies' services, as well as minimum wage and unemployment benefits, considerably interact with and influence unemployment and long-term unemployment ratios, wage levels, duration of periods of unemployment, skills demand, and worker turnover. Moreover, strong indirect effects were detected, e.g. programs aimed at one group of job seekers affected other job seekers and the whole economy. This impacts are sometimes positive and sometimes negative.
http://dx.doi.org/10.7910/DVN/5JDXHS
Keywords: C63; C69; J48; J63; J64; 330; agent-based search and matching model; skills heterogeneity; long-term unemployment; on-the-job search; ALMP evaluation; sensitivity analysis